Photocatalytic Degradation of Dyes: An Overview - Viswanathan, B. (Current Catalysis, 2018)
Introduction: The photocatalytic degradation of dyes has been investigated throughout the world irrespective of the level of science in that country. The normal variables considered are the concentration of oxidising species, the concentration of the dye employed, the catalyst used and intensity and source of photons applied for degradation studies. The kinetic data obtained on the decolorization have usually been treated with pseudo first order kinetic expression even there are some exceptions. Conclusion: This presentation addresses the limitations of the consideration of this topic under these experimental parameters and shows how the study can be directed in future.
Keywords: dye